The Eye in the Neck: Removal of a Sewing Needle from the Posterior Pharyngeal Wall - Samit N. Unadkat; Rishi Talwar; Neil Tolley (Case Reports in Medicine)
Foreign body ingestion is a frequent presenting complaint to most emergency departments but the finding of a sewing needle in the posterior pharynx particularly is a rare finding. We report a case of a male patient with a sewing needle lodged in the posterior pharynx despite a history suggestive of chicken bone ingestion, absent clinical features, and negative flexible endoscopic examination. The needle was only identified through cervical spine radiographs. Even subsequent pharyngoscopy, laryngoscopy, and upper oesophagoscopy all proved to be unremarkable with the patient eventually requiring a left neck exploration to remove the needle. The case outlines the importance of simple radiography in suspected foreign body ingestion, even though clinical and endoscopic findings may be unremarkable.